The freedom of movement of persons in accordance with the new family models. A view from the Pancharevo sentence - Sánchez Cano, Mª Jesus (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The work of the CJEU has been particularly highlighted in relation both to the right to respect for private and family life (Art.7 CFEU) and to the freedom of movement and residence to which all citizens of the Union are entitled (Art.21 TFEU 2 and Art.45 CFEU), with regard to which the European Court has sought to provide an interpretation that guarantees the continuity of family relations in cross-border cases, as opposed to the limitations or restrictions established by the public authorities of each State. With this objective and with the purpose of encouraging the freedom of movement of all citizens of the Union and similar, the CJEU has interpreted principles such as non-discrimination on nationality (Art.18 TFEU and Art.21 CDFUE), completing the notion of European citizenship (Art.20 TFEU).
Keywords: private and family life; freedom of movement; principle of non-discrimination; European citizenship